Effective Post‐Signing Market Check or Window Dressing? The Role of Go‐Shop Provisions in M&A Transactions. (13th January 2014) - Jeon, Jin Q; Lee, Cheolwoo
Abstract This paper examines the use of go‐shop provisions in M&A. We find that go‐shop deals tend to have higher deal premiums and receive more competing bids while the length of the go‐shop period does not affect deal premium and competition. Also, deals are less likely to be completed when a go‐shop provision is included and when the go‐shop length is longer. However, go‐shops have no effect on the completion of high premium deals. We also find that the presence of a go‐shop provision leads to a positive market reaction to deal announcements. Overall, our findings support the proposition that go‐shops reflect the efforts of target managers to fulfill the Revlon duties in the form of a post‐signing market check, which is consistent with stewardship theory.